The Design For An Aerial Monitoring System For Environmental Surveillance Applications - Amir Farhan, Mohd Rasidi (2022)
Natural hazards are occurring at an alarming rate around the world. Before beginning suitable rescue and aid efforts in a disaster-stricken area, it is required to conduct an investigation. Military officials often must patrol risky locations to seek any potential threat, illegal activity, or intrusion within a country's borders that can put the lives of inhabitants in jeopardy. Such locations carry a very significant risk to human life. Other than UAVs or high-tech drones, nanosatellites such as CanSat can be utilized for aerial surveillance and monitoring in Unmanned Aerial Systems (UAS). It can also provide real-time data to a control room or computer. The telemetry type of CanSat is utilized in this project to gather and send data from the flight and environmental conditions in real-time for processing by a base station. The major parts employed in the CanSat design are the microcontroller and power supply. In addition to those stated above, the mission may incorporate other elements. These FPGAs in spacecraft enable more efficient processing by transferring the design to hardware. There are many difficulties in designing nanosatellites such as CanSat. Firstly, is difficult in designing nanosatellites using FPGAs technology and integrate them with the sensors because FPGAs consist of simple logic elements, which can be combined to implement the peripherals previously mentioned, but only interact with most other digital electronics. The design of CanSat needs to fit the microcontroller as the main unit with all the major subsystems found in a satellite, such as power, sensors, and a communication system, into the minimal volume. Besides, using those microcontrollers is less efficient to get the high-speed real-time data in an aerial surveillance application. The primary goal of this work is to develop a telemetry CanSat utilizing an FPGA DE10-Lite Development Board (Altera Max 10), Arduino Uno R3 Microcontroller, and an appropriate sensor (Temperature and humidity sensor, GPS Module, Barometric Sensor, Accelerometer Sensor) and a wireless communication system. The CanSat will then monitor and collect real-time telemetry data from a ground station. Finally, the telemetry data from various places and altitudes below 1km will be analyzed.